An Oriental Wood Borer, Heterobostrychus aequalis (Waterhouse) (Insecta: Coleoptera: Bostrichidae) - Robert E. Woodruff; Thomas R. Fasulo (EDIS)
EENY-364, a 4-page illustrated fact sheet by Robert E. Woodruff and Thomas R. Fasulo, describes this serious pest of lumber and stored wood products which has been found and intercepted at Florida ports, and is now established in the wild. Includes sections on synonymy, distribution, description, biology, hosts, economic importance, and selected references. Published by the UF Department of Entomology and Nematology, January 2006.